Collaborating for innovation: The inhibiting role of constraints - Athanasia D. Nalmpanti; Chee Yew Wong; Pejvak Oghazi (Journal of Innovation & Knowledge (JIK), 2024)
There is a growing recognition that firms increase their collaboration breadth by opening their boundaries to more innovation partners, sourcing and integrating complementary knowledge, skills, and resources and, in turn, improving their innovation performance. However, not all firms benefit equally from collaboration breadth. We argue that the literature has not considered important contingency factors that can mitigate such benefits. This paper enhances understanding of the relationship between collaboration breadth and innovation performance by contending, and empirically confirming, that the magnitude and direction of this association depend on the type of constraints the firm faces. Drawing on organizational learning theory, it is argued that firms encountering financial, knowledge, and institutional innovation constraints will compromise the effects of their openness. The empirical findings suggest that innovative firms face challenges balancing trade-offs between a broad collaboration network and high financial, knowledge, and institutional constraints.
Keywords: O32; L24; D83; 650; Collaboration breadth; Innovation; Performance; Innovation constraints; Open innovation